Using recurrence quantification analysis descriptors for protein sequence classification with support vector machines - Mitra, Joydeep; Mundra, Piyushkumar; Kulkarni, B. D.; Jayaraman, Valadi K. (Journal of Biomolecular Structure & Dynamics, 2007)
In this work, we integrate a non-linear signal analysis method, recurrence quantification analysis (RQA), with the well-known machine-learning algorithm, support vector machines for the binary classification of protein sequences. Two different classification problems were selected, discriminating between aggregating and non-aggregating proteins and mostly disordered and completely ordered proteins, respectively. It has also been shown that classification performance of SVM models improve on selection of the most informative RQA descriptors as SVM input features.